2020
DOI: 10.1002/bmc.4949
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐neuraminidase activity of chemical constituents of Balanophora involucrata

Abstract: Balanophora involucrata J. D. Hooker has been known to possess potential anti‐inflammatory and antibacterial activities; however, its antiviral activity has not been evaluated so far. In order to find new neuraminidase inhibitors (NAIs), the neuraminidase (NA) inhibition activity of different B. involucrata extracts was evaluated. In this study, an in vitro NA inhibition assay was performed to identify which extract of B. involucrata exhibits (maximal) inhibitory activity against NA. Ultra high performance liq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…As shown in Table S1 , 41 compounds were identified or characterized in the mixed extracts of 209 samples based on standards and relevant literature [ 3 , 23 – 27 ]. The 41 compounds included 17 phenolic acids and their derivatives, 19 flavonoids and their derivatives, and 5 others.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Table S1 , 41 compounds were identified or characterized in the mixed extracts of 209 samples based on standards and relevant literature [ 3 , 23 – 27 ]. The 41 compounds included 17 phenolic acids and their derivatives, 19 flavonoids and their derivatives, and 5 others.…”
Section: Resultsmentioning
confidence: 99%
“…HPLC analysis detected quercitrin, myricetin, afzelin, quercetin, and amentoflavone in TOF. Several researches showed that quercitrin blocks IAV infection by controlling TLR signaling and inhibiting NA and NS1 proteins in the docking studies ( Ahmad et al., 2015 ; Ling et al., 2020 ; Sun et al., 2020 ; Tang et al., 2023 ). Our previous study showed that quercetin inhibits IAV attachment and entry at an early infection ( Cho and Ma, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Antiviral Activity [37] Neuraminidase inhibition: IC 50 = 311.76 µM (Oseltamivir acid IC 50 = 280 µM). Myeloperoxidase inhibition [38] IC 50 = 2.0 ± 0.2 µM Prevention of metal toxicity effects [39] Almost 100% HepG2 cell line viability when treated with 1 µM + 15 µM MeHg (50% viability when only treated with 15 µM MeHg).…”
Section: In Vitro Activitiesmentioning
confidence: 99%
“…Further investigations are necessary to explain the cytoprotective mechanism of the compound. Quercitrin (9) also presents a moderate antiviral activity by inhibition of neuraminidase (NA) [37], a viral enzyme common in human influenza viruses, which is essential for the virus release from infected cells to the neighboring cells of the respiratory tract [69]. It has also been reported that quercitrin (9) inhibits the activity of myeloperoxidase, with an IC 50 of 2.0 µM [38], a result that hints at its possible role in reducing endothelial dysfunction and consequently that the protective effect of 9 should be evaluated in an atherosclerosis model.…”
Section: D-glcpymentioning
confidence: 99%